2010
DOI: 10.1002/rcm.4780
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐state‐derivation ion detection using a super‐conducting nanostructure device for mass spectrometry

Abstract: Mass spectrometry (MS) is a method of analyzing ions based on their mass/charge (m/z) ratios. The m/z peak identification requires speculation on the ionic charge states. This problem can be solved by using superconducting junction devices to measure the kinetic energies of single molecules. However, the kinetic energy measurement is followed by the dead time of 1-20 ms, which is fatally slow for modern high-resolution time-of-flight (TOF) analyzers. In this paper, we demonstrate that a superconducting nano-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…1(e). This result ensures that the charge-state derivation 4) for singly and doubly charged lysozyme ions accelerated by a higher acceleration voltage of 17.5 kV is practical. The transition width of the detection efficiency ÁI=I c is defined as the relative bias current width for the detection efficiency reduction from 0.1 to 0.001.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1(e). This result ensures that the charge-state derivation 4) for singly and doubly charged lysozyme ions accelerated by a higher acceleration voltage of 17.5 kV is practical. The transition width of the detection efficiency ÁI=I c is defined as the relative bias current width for the detection efficiency reduction from 0.1 to 0.001.…”
mentioning
confidence: 97%
“…S uperconducting nano-stripline detectors (SSLDs) have been widely investigated because of short response time and high detection efficiency, which are crucial to mass spectrometry (MS) [1][2][3][4][5][6][7] or quantum communication. [8][9][10][11][12][13][14][15][16][17][18][19][20] The SSLDs are expected to realize a high mass resolution and the mass-independent detection sensitivity at the same time, both of which are among the specifications of an ideal mass detector.…”
mentioning
confidence: 99%
“…Suzuki at al. [41] demonstrated that, behind the nanosecond response, the short recovery time, the wide mass range, and low noise, SSPDs also possess the charge-state derivation ability. This was possible by subtracting data at different bias currents that determine detectable lower threshold energies of ions.…”
Section: Charge Discrimination and True Mass Spectrometrymentioning
confidence: 99%
“…The SSLDs have already been applied to detection of a variety of particles such as a single photon [1], a macromolecule [2], a neutron [3], etc. The present phase in the development is to array multiple SSLDs for enhancing a detecting area or for making an imager.…”
Section: Introductionmentioning
confidence: 99%